PENGARUH BAURAN PEMASARAN PRODUK, GAYA HIDUP & HIJAU TERHADAP KEPUTUSAN PEMBELIAN PRODUK THE BODY SHOP DI JAKARTA - Bernard Edwin Silaban; Emanuella Annastasia (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2019)
The objective of this research are to see wether product marketing mix, lifestyle and green marketing mix do influence the purchasing decision of the product of the body shop in Jakarta and what about the post purchase behaviour. The results show that product marketing mix, lifestyle and green marketing mix simultaneously and partially influence the purchasing decision significantly. The other result also shows that the post purchase behavior of the consumers are being satisfactory.